Genetics of wild, whirling disease resistant rainbow trout populations in Colorado - Avila, Brian W.; Fetherman, Eric R.; Winkelman, Dana L.; Baerwald, Melinda R. (Frontiers in Freshwater Science, 2025)
IntroductionMyxobolus cerebralis, the parasite responsible for salmonid whirling disease, was unintentionally introduced to and became established in Colorado in the 1990s. Mortality of young-of-year fish due to infection by M. cerebralis resulted in recruitment failure and subsequent significant declines in Rainbow Trout (Oncorhynchus mykiss) populations. The complex multistage lifecycle of M. cerebralis makes it difficult to eradicate and manage, and hatchery control strategies do not work in the wild. A viable method that has been utilized for wild populations is enhancing host resistance. Myxobolus cerebralis resistant Rainbow Trout were discovered at a hatchery in Germany and subsequently incorporated into Colorado's brood stock program. Since 2004, M. cerebralis resistant strains have been stocked into all major Colorado coldwater drainages to re-establish Rainbow Trout populations after whirling disease-related declines, with documented survival and reproduction of stocked disease resistant fish.Methods and resultsGenetic population assignment tests (via putatively neutral microsatellite markers) were used to monitor the stocked populations and indicated that, after only a few years, many of the individuals in these populations unexpectedly assigned to genetic strains that were historically susceptible to M. cerebralis. To further investigate the genetic composition of these fish, a single nucleotide polymorphism (SNP) panel was used to determine the percent genetic composition of resistant strain in these individuals. Microsatellites and SNPs provided similar results, indicating a low percentage of ancestry from the resistant strain in these fish, but they continued to survive exposure to M. cerebralis, suggesting that these individuals possessed genetic loci necessary for resistance. Finally, a quantitative trait locus (QTL) region (termed WDRES-9) was used to identify individuals with alleles associated with disease resistance. Implementation of the WDRES-9 QTL test allowed for more accurate determination of M. cerebralis resistant individuals within wild populations and better described their variability in resistance.DiscussionOverall, reintroductions and genetic monitoring required a suite of tools to understand the effects of M. cerebralis exposure on the genetic resistance of wild fish populations over time.